Fatal hepatotoxicity secondary to nimesulide - Merlani, Giorgio; Fox, Mark; Oehen, Hans-Peter; Cathomas, Gieri; Renner, Eberhard L.; Fattinger, Karin; Schneemann, Markus; Kullak-Ublick, Gerd A. (European journal of clinical pharmacology, 2001)
This report describes a 57-year-old female patient with chronic lumbago, who died from the sequelae of acute liver failure induced by nimesulide medication. Nimesulide is a non-steroidal anti-inflammatory drug (NSAID) which preferentially inhibits cyclo-oxygenase 2 and has been associated with a total of 13 reported cases of severe liver injury including our case. On the basis of the literature reports, the following features of nimesulide-associated hepatotoxicity were identified: female sex (84% of cases), age (mean age 62 years), jaundice as a primary manifestation (90%) and the absence of peripheral blood eosinophilia. The average duration of therapy of the published cases was 62 days (range 7-180 days). Based on spontaneous reports to the World Health Organization, nimesulide induces a high proportion of severe adverse hepatic reactions compared with other NSAIDs registered in Switzerland. Hepatotoxicity thus represents an important risk factor of nimesulide usage.[PUBLICATION ABSTRACT]